Mechanistic Study of N-Bromosuccinimide Oxidation of Ethyl Amine Catalyzed by Palladium(II) in Alkaline Medium : A Kinetic Approach - Kumar, Ashutosh; Pratap, Bhanu (Asian Journal of Chemistry, 2012)
The kinetics of oxidation of ethyl amine by N-bromosuccinimide in the presence of alkaline solution of palladium(II) chloride as homogeneous catalyst has been investigated at 303 K. A1 : 1 stoichiometry has been observed. The reaction exhibits a zero order rate dependence with respect to amine and first order at low concentration of N-bromosuccinimide tending to zero order at high concentration of N-bromosuccinimide. A positive fractional order is observed in the case of Pd(II) whereas ionic strength, [OH–] and Hg(OAc)2 do not influence the oxidation rate. The reaction follows negligible effect on addition succinimide and chloride ion. The activation parameters have been evaluated from the Arrhenius plot. Mechanistic steps are discussed and the rate law derived was found to confirm the observed kinetic results.